2006
DOI: 10.1523/jneurosci.1202-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intraneuronal β-Amyloid Aggregates, Neurodegeneration, and Neuron Loss in Transgenic Mice with Five Familial Alzheimer's Disease Mutations: Potential Factors in Amyloid Plaque Formation

Abstract: Mutations in the genes for amyloid precursor protein (APP) and presenilins (PS1, PS2) increase production of ␤-amyloid 42 (A␤ 42 ) and cause familial Alzheimer's disease (FAD). Transgenic mice that express FAD mutant APP and PS1 overproduce A␤ 42 and exhibit amyloid plaque pathology similar to that found in AD, but most transgenic models develop plaques slowly. To accelerate plaque development and investigate the effects of very high cerebral A␤ 42 levels, we generated APP/PS1 double transgenic mice that coexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

275
3,827
19
41

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,886 publications
(4,162 citation statements)
references
References 61 publications
275
3,827
19
41
Order By: Relevance
“…Previous studies have demonstrated that long‐term RF‐EMF exposure may have beneficial effects on cognitive deficits of AD transgenic mice [Arendash et al, 2010; Jeong et al, 2015], and this effect might be related to reduced Aβ deposition. Therefore, we used the 5xFAD transgenic mouse model, which shows AD‐like pathology, such as early Aβ plaque formation in brain parenchyma and behavioral deficits [Oakley et al, 2006]. We exposed 5xFAD mice to RF‐EMF for 3 months to evaluate the effect of RF‐EMF on memory impairment and Aβ pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that long‐term RF‐EMF exposure may have beneficial effects on cognitive deficits of AD transgenic mice [Arendash et al, 2010; Jeong et al, 2015], and this effect might be related to reduced Aβ deposition. Therefore, we used the 5xFAD transgenic mouse model, which shows AD‐like pathology, such as early Aβ plaque formation in brain parenchyma and behavioral deficits [Oakley et al, 2006]. We exposed 5xFAD mice to RF‐EMF for 3 months to evaluate the effect of RF‐EMF on memory impairment and Aβ pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, transgenic mice overexpressing hAPP without AD‐related mutations, like I5, barely develop any Aβ deposits at high age (Mucke et al ., 2000). However, mice overexpressing mutant hAPP Swedish display Aβ deposits starting at around 10 months of age, for example Tg2576 (Hsiao et al ., 1996), while mice overexpressing mutant hAPP Swedish in combination with mutant γ ‐secretase components generate Aβ deposits even faster, for example 5xFAD (Oakley et al ., 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Here, we assessed SUMO1 conjugation during alterations of proteostasis, as observed during aging and the development of AD‐like pathology. For this purpose, we crossed the His 6 ‐HA‐SUMO1 knock‐in (KI) with the 5XFAD mouse model that rapidly recapitulates major features of AD, including neuronal loss in hippocampal and cortical regions, and age‐dependent synapse loss (Oakley et al., 2006). We generated double mutant mice that are referred to here as KI/AD; non‐KI and non‐AD mice were used as controls, and are referred to as KI/WT, WT/AD, and WT/WT.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we used the 5XFAD mouse model that shows clear age‐related AD features such as amyloid deposition, synaptic loss, and age‐related cognitive decline (Oakley et al., 2006). Strikingly, we found age‐related alterations of SUMO1 conjugation in this AD model but did not detect any significant changes in SUMO1 conjugation related to an increased amyloid burden.…”
Section: Introductionmentioning
confidence: 99%